M/OTHERING: A Database of Terracotta Votive Figurines Representing Adults with Subadults from Ancient Italy - Giulia Pedrucci; Ricardo Fernandes; Carlo Cocozza (Journal of Open Archaeology Data)
We introduce the M/OTHERING dataset, an open-access resource for researchers exploring the social and religious dimensions of ancient Italy and beyond. This dataset lists metadata for 2,725 terracotta votive figurines depicting adults with subadults, dating from 625 to 27 BCE, and originating from the historical regions of Etruria, Latium, Magna Graecia, and Sicilia. The upper limit of 27 BCE was chosen to coincide with the end of the Roman Republic and the establishment of the Principate, a major political and cultural transition. While dating remains imprecise for many objects, this boundary provides a meaningful terminus for the dataset’s scope. The dataset includes comprehensive iconographic data along with historical, archaeological, chronological, and spatial metadata, making it a foundational archive for comparative analysis and a crucial tool for large scale meta-analyses. By overcoming language barriers and the inaccessibility of scientific publications or reports that are often only available at local museums and libraries, this dataset facilitates a holistic understanding of maternal imagery, votive practices, and socio-religious dynamics in pre-Roman and Roman Republican Italy at multiple scales.